2018
DOI: 10.32874/shs.2018-02
|View full text |Cite
|
Sign up to set email alerts
|

Institucionalna in zasebna religioznost v severovzhodni Sloveniji. Primerjalna analiza slovenskih regij po letu 1969

Abstract: Category: 1.01 Original scientific paper Language: Original in Slovenian (Abstract in Slovenian and English, Summary in English) Key words: religion, northeast Slovenia, statistical regions, privatization of religion Abstract: A comparative analysis of religiosity across Slovenian statistical regions was conducted based on the survey data from the Slovenian Public Opinion project (SPO). It took into consideration available data from 1969 to 2016 and compared four regions of northeast Slovenia (Pomurska, Podrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This decline is most visible in Church participation, the importance of religion in an individual's life, and the decline of trust in the Church (Nikodem & Zrinščak, 2019). Similar trends have been observed among young people (Lavrič, 2019) and students (Boneta, 2016). Ilišin (2014) concluded that students are a relatively homogeneous category in which the majority accepts basic liberal‐democratic principles and considers extreme right‐wing views unacceptable.…”
Section: Theoretical‐conceptual Framework Research Aims and Hypothesessupporting
confidence: 81%
See 3 more Smart Citations
“…This decline is most visible in Church participation, the importance of religion in an individual's life, and the decline of trust in the Church (Nikodem & Zrinščak, 2019). Similar trends have been observed among young people (Lavrič, 2019) and students (Boneta, 2016). Ilišin (2014) concluded that students are a relatively homogeneous category in which the majority accepts basic liberal‐democratic principles and considers extreme right‐wing views unacceptable.…”
Section: Theoretical‐conceptual Framework Research Aims and Hypothesessupporting
confidence: 81%
“…With regard to the general but also Croatian secularization trend, especially among young people (Croccket & Voas, 2006; Lavrič, 2019), the relevant question is to what extent are the consequences of RS in childhood, but also of attending religious education until recently, present in actual religiosity in student age?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations